Influencia de startups en las Ciudades Creativas. Análisis del desempeño de empresas emergentes en la construcción de la Marca Ciudad - Fernández-Torres, María Jesús; Rando-Cueto, Dolores; Rodríguez Vera, Ainhoa del Pino (My University, 2024)
The Creative City concept arises from the field of economic sciences known as ‘creative economy’. In this framework, activities, goods and services with the capacity to dynamise the economy are relevant (Herrera-Medina et al., 2013). For instance, startups are gaining interest as a source of innovation by implementing new technologies to reinvent business models (Aljalahma & Slof, 2022). According to Informa D&B (2022), 62% of Spanish startups are concentrated in Madrid, Catalonia and Andalusia. The objective is to analyse the influence of startups on these autonomous communities and their coverage in the press. A systematic review of scientific literature of more than a hundred registers is carried out, as well as a content analysis of 255 pieces of information published in Google News in 2024. It addresses keys that relate startups, as an economic engine, in the promotion of Creative Cities and in the construction of the City Brand.
Keywords: Nuevas empresas; Marketing; Ciudades; Creative Cities; Startups; News; Press; City Brand; Entrepreneurship; Spain